Neuro-Cognitive Differences in Semantic Processing Between Native Speakers and Proficient Learners of Mandarin Chinese - Lai, Chia-Ho; Hsieh, Shu-Kai; Lee, Chia-Lin; Su, Lily I-Wen; Liu, Te-Hsin; Lu, Chia-Rung; Tsai, I-Ni; Chou, Tai-Li (Frontiers in Psychology, 2021)
The present study aimed to investigate the neural mechanism underlying semantic processing in Mandarin Chinese adult learners, focusing on the learners who were Indo-European language speakers with advanced levels of proficiency in Mandarin Chinese. We used functional magnetic resonance imaging technique and a semantic judgment task to test 24 Mandarin Chinese adult learners (L2 group) and 26 Mandarin Chinese adult native speakers (L1 group) as a control group. In the task, participants were asked to indicate whether two-character pairs were related in meaning. Compared to the L1 group, the L2 group had greater activation in the bilateral occipital regions, including the fusiform gyrus and middle occipital gyrus, as well as the right superior parietal lobule. On the other hand, less activation in the bilateral temporal regions was found in the L2 group relative to the L1 group. Correlation analysis further revealed that, within the L2 group, increased activation in the left middle temporal gyrus/superior temporal gyrus (M/STG, BA 21) was correlated with higher accuracy in the semantic judgment task as well as better scores in the two vocabulary tests, the Assessment of Chinese character list for grade 3 to grade 9 (A39) and the Peabody Picture Vocabulary Test-Revised. In addition, functional connectivity analysis showed that connectivity strength between the left fusiform gyrus and left ventral inferior frontal gyrus (IFG, BA 47) was modulated by the accuracy in the semantic judgment task in the L1 group. By contrast, this modulation effect was weaker in the L2 group. Taken together, our study suggests that Mandarin Chinese adult learners rely on greater recruitment of the bilateral occipital regions to process orthographic information to access the meaning of Chinese characters. Also, our correlation results provide convergent evidence that the left M/STG (BA 21) plays a crucial role in the storage of semantic knowledge for readers to access to conceptual information. Moreover, the connectivity results indicate that the left ventral pathway (left fusiform gyrus-left ventral IFG) is associated with orthographic-semantic processing in Mandarin Chinese. However, this semantic-related ventral pathway might require more time and language experience to be developed, especially for the late adult learners of Mandarin Chinese.